Adaptive vibration condition monitoring technology for local tooth damage in gearboxes. - Gelman, Leonid; Zimroz, R; Birkel, J; Leigh-Firbank, H; Simms, Daniel M.; Waterland, B; Whitehurst, G (Learned and Professional Society Publishers, 2005)
An adaptive approach was applied for local tooth damage diagnostics in gearboxes. The expediency of adaptation was proved experimentally for the new diagnostic feature, the sum of normalized sideband amplitudes. The positive correlation between mesh amplitudes and their sideband amplitudes was found experimentally for the first time. Novel adaptive vibration condition monitoring technology for local tooth damage in gearboxes was developed and experimentally validated. The experimental results showed an increase in effectiveness of the diagnostics when the adaptive technology was used.